Tehniške meritve: zbrano gradivo - Hribernik, Aleš (2017)
Engineering Measurements: Collected Material. Basic measurement methods used commonly to measure physical quantities important in mechanical engineering are presented in this book. Chapter 1 provides some brief definitions of important terms common to all measurement systems and discusses input-output configuration of instruments regarding interfering and modifying inputs and their influence on an instrument’s output. Characteristics of instruments are given in Chapter 2. First, the static characteristics are presented focused on experimental error and measurement uncertainty. Next, the dynamic characteristics are given, with examples of first and second order instruments. Temperature measurement is discussed in Chapter 3. Thermodynamic and international temperature scale are presented first, and then followed by the classical and electrical contact type temperature measuring devices. Finally, different pyrometers are presented for non-contact temperature measurement by radiation. Chapter 4 discusses several electrical systems for displacement measurement and gives the basic idea of digital displacement transducers. Velocity and acceleration measurement, particularly vibration and angular velocity measurements, are presented in Chapter 5. Mechanical, electrical, optical and digital measurement systems are discussed. Chapter 6 discusses strain measurements. Common electrical circuits for strain gages are presented and some simple cases are discussed of uniaxial and biaxial stress state. Strain measurement errors are analysed and the main error sources are emphasised. Chapter 7, concerning pressure measurements, presents: Static pressure measurements applying different fluid and mechanical manometers, low-dynamic electrical pressure measurements using elastic body transducers and high-dynamic pressure measurement with piezoelectric transducers. Flow measurement is discussed in Chapter 8 in a rather conventional way, starting with flow obstruction methods, positive-displacement methods and different electric and magnetic flowmeters. Basic principles of fluid velocity measurements using ultrasound and laser methods are presented as well.
Keywords: measurement methods; measurement systems; sensors; mechanical engineering; physical quantitys